2007
DOI: 10.1111/j.1469-8749.2007.00129.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of severe major anomalies in children conceived by intracytoplasmic sperm injection

Abstract: The neurodevelopmental outcome of children born after intracytoplasmic sperm injection (ICSI) is controversial. We compared the medical and developmental outcome of 34 singletons born after ICSI (20 males, 14 females; mean ages of 18mo and 40mo [SD 9mo]; range 2y 10mo–4y 8mo) with 39 case control studies (21 males, 18 females; mean ages of 18mo and 40mo [SD 4mo]; range 3y–4y 1mo). Each child was assessed physically and tested in three development domains (fine motor, gross motor, and language). Five children b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…In another study involving a small number of patients, there was no significant difference in occurrence of major malformations in the ICSI group (5/34, 14.5%) compared with the natural conception group (2/39, 5%), but the incidence of severe major malformations was significantly increased in the ICSI group (11.8 vs. 0%) [48] .…”
Section: Review Of the Literaturementioning
confidence: 87%
“…In another study involving a small number of patients, there was no significant difference in occurrence of major malformations in the ICSI group (5/34, 14.5%) compared with the natural conception group (2/39, 5%), but the incidence of severe major malformations was significantly increased in the ICSI group (11.8 vs. 0%) [48] .…”
Section: Review Of the Literaturementioning
confidence: 87%
“…In addition, there is an apparent increase of Angelman syndrome (OMIM no. 105830) cases presenting with the rare methylation defect at SNRPN (15)(16)(17)(18). It has been suggested that IVF-associated cases of Beckwith-Wiedemann and Angelman syndrome may represent the tip of the iceberg (19), potentially reflecting a larger number of epigenetic changes in the IVF population.…”
mentioning
confidence: 99%
“…However, a mutation in the KIF21A gene, which was identified in congenital fibrosis of extraocular muscles type 1, has been reported in cases of MS accompanied by additional eye movement disorder (3). In the medical literature, a case of MS and a patient with Hanhart syndrome involving Moebius sequence in relation with intracytoplasmic sperm injection (ICSI), which is one of the assisted reproductive techniques, have been reported (4,5). Our patient was born by way of in vitro fertilization and we could no other case reports in relation with in vitro fertilization in the medical literature.…”
Section: Introductionmentioning
confidence: 81%
“…Studies have shown that some major and/or minor anomalies occur more commonly in babies of mothers who became pregnant by way of assisted reproductive techniques compared with groups that were pregnant through intercourse (2). A case of MS and a case of Hanhart syndrome (MS-associated syndrome) in relation with the intracytoplasmic sperm injection method have been reported previously (4,5). Although studies conducted in recent years have reported that there was no increase in the general risk of congenital anomaly in relation with in vitro fertilization, an increased risk has been reported in under certain conditions (10).…”
Section: Discussionmentioning
confidence: 99%